Applied e-learning and e-teaching in higher education - Donnelly, Roisin; McSweeney, Fiona (Information Science Reference, 2009)
"This book presents international practices in the development and use of applied e-Learning and e-Teaching in the classroom in order to enhance student experience, add value to teaching practices, and illuminate best practices in the area of e-Assessment. This book provides insight into e-Learning and e-Teaching practices while exploring the roles of academic staff in adoption and application"--Provided by publisher.